Possibility to use waste tire waste in the composition of mixtures for the manufacture of cement blocks (Research, Society and Development, 2020)
The modern lifestyle has led to an increase in the amount of solid waste in the world, and waste tires are one of the most generated. Annually billions of tons of waste tires are produced, so in this study, we sought to reuse them to make materials for civil construction. For this, a laboratory research was carried out where samples were made in 50 x 100 mm cylinders with traces of 0, 10, 15 and 20% (by weight) of waste, in addition to cement, natural sand and water. The granulometric distribution of waste tires and sand was also carried out. And, with the samples in cylinders, the physical and mechanical properties were evaluated, such as water absorption and apparent density, in addition to the analysis of the mechanical resistance to compression and the modulus of elasticity. The results showed that the granulometric distribution of the tire residue fits as a fine aggregate, similar to the sand granulometry. The water absorption rate of the waste specimens was less than 10%. However, the mechanical resistance decreases proportionally as the amount of tire waste has increased. However, when analyzing the behavior of the stress x strain curves, the specimens containing residues, became more flexible, as they are capable of supporting loads beyond the maximum stress. In this way, the resistance and the ability to absorb energy were increased. We concluded that it is possible to incorporate certain quantities of waste tires in blocks for civil construction, but without a structural function.